The Impact of Media Social on Mental Health - Puti Amalia; Feri Catur Yuliani (Medical Studies and Health Journal (SEHAT), 2024)
Excessive social media use has been linked to increased anxiety, depression, and stress in teens. This study aims to examine the influence of the intensity of social media use on levels of anxiety and depression in adolescents. The research method used was a systematic literature review using PRISMA guidelines, which involved in-depth analysis of articles obtained from reputable international databases. The research results show that intense use of social media, especially image-based platforms such as Instagram, contributes significantly to increased anxiety and depression in adolescents. The implications of this research indicate the importance of developing effective and evidence-based mental health interventions to reduce the negative impact of social media on the mental well-being of adolescents.